Bringer of dust - Miro, J. M. (Miro, J. M. Talents trilogy, 2024)
"In this highly anticipated second book in the Talents Trilogy, the world of the dead is closer than you think. Agrigento, Sicily, 1883. With the orsine destroyed, Cairndale lies in ruins, and Marlowe has vanished. His only hope of rescue lies in a fabled second orsine-long-hidden, thought lost-which might not even exist. But when a body is discovered in the shadow of Cairndale, a body wreathed in the corrupted dust of the drughr, Charlie and the Talents realize there is even more at stake than they'd feared. For a new drughr has arisen, ferocious, horned, seemingly able to move in their world at will-and it is not alone. A malevolent figure, known only as the Abbess, desires the dust for her own ends. And deep in the world of the dead, a terrible evil stirs-an evil that the corrupted dust just might hold the secret to reviving or destroying forever. So the dark journey begun in Ordinary Monsters surges forward, from the sinister underworld of the London exiles, to the mysteries of a sunlit villa in nineteenth-century Sicily, to the deep catacombs hidden under Paris. Against bone witches, mud glyphics, and a house of twilight that exists in a netherworld all its own, the Talents must work together-if they are to have any hope of staving off the world of the dead, and saving their long-lost friend"--